2017
DOI: 10.1167/17.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Sustained smooth pursuit eye movements with eye-induced reverse-phi motion

Abstract: The gain and speed of smooth pursuit eye movements quickly drop whenever a moving tracked target disappears behind an occluder. The present study tests to what extent pursuit maintenance after target disappearance depends on the occluder's characteristics. In all experiments, a target moving for 2500 ms, (or 1250 ms) at 13.3°/s (or 26.6°/s), disappears behind an occluder for 700 ms (or 350 ms). Participants are asked to maintain their pursuit eye movements as long as possible after target disappearance. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The ability of pursuit to predict the future trajectory of target motion is also illustrated by the pursuit of targets that momentarily disappear from view. When the target is removed from view after pursuit is under way, pursuit initially slows down and then speeds up again as the expected time of reappearance of the target approaches (e.g., Becker & Fuchs 1985, Bennett & Barnes 2004, Portron & Lorenceau 2017. Barnes & Collins (2008) found that when the target disappeared at or shortly after the onset of target motion, eye velocity continued to increase, albeit at rates below those found with a continuously visible target.…”
Section: Pursuit During the Brief Disappearance Of A Moving Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of pursuit to predict the future trajectory of target motion is also illustrated by the pursuit of targets that momentarily disappear from view. When the target is removed from view after pursuit is under way, pursuit initially slows down and then speeds up again as the expected time of reappearance of the target approaches (e.g., Becker & Fuchs 1985, Bennett & Barnes 2004, Portron & Lorenceau 2017. Barnes & Collins (2008) found that when the target disappeared at or shortly after the onset of target motion, eye velocity continued to increase, albeit at rates below those found with a continuously visible target.…”
Section: Pursuit During the Brief Disappearance Of A Moving Targetmentioning
confidence: 99%
“…The finding that pursuit can continue across periods of target disappearance supports the conclusion that internal representations of the motion path, derived from memory or from cues, are effective stimuli for pursuit. Pursuit across periods of occlusion is constrained to such a large degree by the motion seen prior to the occlusion, the motion expected after the occlusion, and the perceptual characteristics of the occluder (Portron & Lorenceau 2017) that pursuit is more likely to be due to internal representations derived from characteristics of the stimulus or events than to arbitrarily imagined signals or to willful direction of the eye. People cannot do with pursuit eye movements what they can do easily with smooth movements of the arm in darkness, namely initiate a smooth series of movements in any chosen pattern (Krauzlis 2004) [although Becker & Fuchs (1985) claimed that two of their well-practiced subjects could].…”
Section: Pursuit During the Brief Disappearance Of A Moving Targetmentioning
confidence: 99%
“…A second aspect, more technical, must also be considered: the speed of the tracked target was between 16 and 21°/s depending on the patterns, and chosen to allow good tracking in the tracking phase. However, the endogenous generation of smooth pursuit on the flickering background should probably occur at a lower speed to “catch” the illusory motion that allows generating smooth pursuit regarding the stimulus parameters used in this experiment (Lorenceau, 2012; Portron and Lorenceau, 2017). This mismatch between the speed of the tracked target and the eye velocity needed to endogenously generate smooth pursuit can explain, at least in part, the difficulties encountered by participants to freely reproduce the trajectories of the moving target.…”
Section: Discussionmentioning
confidence: 99%
“…On a single frame, all disks had the same luminance, and all disks changed their contrast polarity at 10 Hz, switching from lighter than the background to darker, and reverse. This flickering stimulus is designed to allow endogenously generating SPEM, as shown in a previous study (Lorenceau, 2012; Portron and Lorenceau, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Note that the eye-movements are not explicitly drawn as graphic traces on the screen, but are nevertheless seen by the “eye-writer” as a faint wake produced by the retinal slip. The ease with which participants generate SPEM depends on the stimulus characteristics, such as the contrast of the disks, and the frequency of light-to-dark and dark-to light alternations (Portron and Lorenceau, 2017). During the training sessions, these parameters were interactively adjusted depending on the participants’ report of seeing an illusory motion during their eye-movements.…”
Section: Methodsmentioning
confidence: 99%